Measurement Simulation System of Fringe Projection Profilometry Based on Ray Tracing - Qiushuang Zhang; Mingyi Xing; Hongbin Li; Xu Li; Tingli Wang (IEEE Access, 2023)
Fringe projection profilometry (FPP) plays an important role in the quality control of complex surface workpieces. Simulation using realistic image synthesis referring to physical sensors provide valid measures for the design and optimization of FPP systems. In the simulation of FPP, ray tracing can simulate the fringe image acquisition process, considering the comprehensive influence of light source, camera and object attributes. Therefore, a measurement simulation system of FPP based on ray tracing is developed in this paper. The simulation model and measurement principle of FPP are introduced. On this basis, the methodology of simulating camera imaging by ray tracing is proposed, including scene construction, ray generation and gray value calculation. Principle experiments are carried to verify the accuracy and efficiency of simulation system, and comparative experiments are conducted for demonstrating its reproducibility to physical system. The proposed system provides a convenient and accurate mean for analyzing measurement errors and optimizing inspection strategy.